Gifted pain [videorecording (Blu-Ray)] - Jon, Tobias; Jon, Tobias; Duncan, Sarah Jane; Baldwin, Dylan; Collins, Karl (Bojman Films, 2025)
A loner struggles with childhood tragedy. Seeking refuge, he immerses himself in martial art films. A life changing moment releases unknown abilities, taking him closer to solving the mystery of his past. But the truth will come at a cost.